Novel intravesical therapeutics in the treatment of non-muscle invasive bladder cancer: Horizon scanning - Ward, Kelly; Kitchen, Mark O; Mathias, Suresh-Jay; Khanim, Farhat L; Bryan, Richard T. (Frontiers in Surgery, 2022)
Introduction: Non-muscle-invasive bladder cancer (NMIBC) is a common and heterogeneous disease; many patients recur or progress to muscle-invasive tumours. Intravesical drug therapy is a pillar in the current management of NMIBC; notwithstanding, Mitomycin C (MMC) and Bacillus Calmette-Guerin (BCG) have numerous limitations including international supply issues, and local and systemic toxicity. Here we review novel intravesical therapeutic options and drug delivery devices with potential for clinical use in the treatment of NMIBC. Methods: PubMed, ClinicalTrials.gov and Cochrane Library searches were undertaken. Systematic reviews, meta-analyses, randomised controlled trials, single-arm clinical trials and national/international conference proceedings were included. Results: Novel intravesical drugs, including chemotherapeutic agents, immune checkpoint inhibitors, monoclonal antibodies and gene therapies, have demonstrated varying efficacy in the treatment of NMIBC. Current evidence for the majority of treatments is mostly limited to single-arm trials in patients with recurrent NMIBC. Various novel methods of drug delivery have also been investigated, with encouraging preliminary results supporting the intravesical delivery of hyperthermic MMC and as MMC hydrogel formulations. Conclusions: Novel therapeutic agents and drug delivery systems will be important in the future management of NMIBC. As our understanding of the molecular diversity of NMIBC develops, molecular subtyping will become fundamental in the personalisation of intravesical treatments. Further randomised studies are urgently required to investigate the efficacy of novel intravesical treatments and novel regimens, in comparison to current standards-of-care, particularly in the context of the international BCG shortage.